Plant collecting in São Tomé and Príncipe—collectors and their itineraries during the colonial period - Figueiredo, Estrela; Smith, Gideon F.; F. De Lima, Ricardo (Phytotaxa, 2024)
The history of vascular plant collecting on the islands of São Tomé and Príncipe, from the earliest times up to the independence of the country in 1975 is provided, along with biographical information on all the collectors that could be traced, with notes on their itineraries, collecting localities, and collections. Aspects of the social environment prevalent in São Tomé and Príncipe at the time that historical collections were made are highlighted and contextualised to enable an improved understanding of connections between scientific-botanical endeavour, colonialism, and slavery on São Tomé and Príncipe.